Total synthesis of the phytotoxic agent herbarumin II using butane diacetals of glycolic acid as building blocks - Diez, E; Dixon, D; Ley, S; Polara, A; Rodriguez, F (2003)
The total synthesis of the phytotoxic agent herbarumin II has provided an ideal stage to exploit the utility of butane diacetal (BDA) desymmetrised glycolic acid as a primary building block.